Logística inversa: Estrategias de recuperación en empresas zulianas de derivados lácteos - Huérfano Piñeiro, Eneida María (2017)
Reverse logistics is a concept of recent introduction and little known in companies of dairy products sector in Zulia state (Venezuela), most of them have started in their implementation; either as part of an after-sales service, or as part of the production and / or marketing process. Apparently, it only needs to be structured integrally and give it a strategic dimension.In this article processes and operations binding aspects of Zulia dairy circuit with reverse logistics are presented. In this sense, the reverse logistics in the supply chain of dairy derivatives companies in Zulia is characterized. Guide strategies and reverse logistics activities as socially responsible practices are submitted. This becomes challenging, since implementing a reverse logistics system as an essential and potential strategy is a difficult issue given the country’s socio-economic and political situation. Reflections are presented to face the barriers in retro logistics implementation. The main one being the need to internalize in each individual rational resources using and acting effectively to engage with private companies and state organizations in the sustainable institutions operations.